BCL2 Expression at Post-Induction and Complete Remission Impact Outcome in Acute Myeloid Leukemia - Bilbao-Sieyro, Cristina (Diagnostics (Basel), 2020)
Advances in acute myeloid leukemia (AML) genomics and targeted therapies include the recently approved BCL2 inhibitor venetoclax. The association between BCL2 expression and patient outcome was analyzed in a series of 176 consecutive AML patients at diagnosis (Dx), post-induction (PI), complete remission (CR) and relapse (RL). Levels increased significantly at relapse (mean 1.07 PI/0.96 CR vs. 2.17 RL, p = 0.05/p = 0.03). In multivariate analysis, high BCL2-Dx were marginally associated with worse progression-free survival, while high PI levels or at CR had an independent negative impact on outcome (PI: HR 1.58, p = 0.014; CR: HR 1.96, p = 0.008). This behavior of high PI or CR BCL2 levels and increased risk was maintained in a homogeneous patient subgroup of age <70 and intermediate cytogenetic risk (PI: HR 2.44, p = 0.037; CR: HR 2.71, p = 0.049). Finally, for this subgroup, high BCL2 at relapse indicated worse overall survival (OS, HR 1.15, p = 0.05). In conclusion, high BCL2 levels PI or at CR had an independent negative impact on patient outcome. Therefore, BCL2 expression is a dynamic marker that may be useful during AML patient follow up, and BCL2 levels at PI and/or CR may influence response to anti-BCL2 therapy.